Diagnosis of Approximal Caries after Delayed Scanning of Photostimulable Phosphor Plates - Zahra Ghoncheh; Yasaman Kheirandish; Hanieh Kaviani; Mohammad Javad Kharazi Fard; Kurosh Sadeghi (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Considering the high diagnostic accuracy and wide dynamic range of photostimulable phosphor plates (PSPs), they can be a good alternative for radiographic films. Purpose: This study was aimed to assess the effects of delay in scanning PSPs on the diagnostic accuracy of detection of approximal caries. Materials and Method: Radiographs from fifty-two extracted molar and premolar teeth were radiographed using DIGORA PSP (Soredex Corporation, Helsinki, Finland). The teeth were either intact or with non-cavitated approximal caries. The plates were scanned immediately (time zero) and at 10 min, 30 min, 60 min and 120 min after exposure. Sixty-five images were obtained and evaluated for presence or absence of approximal caries by two oral and maxillofacial radiologists and 2 restorative specialists. The diagnostic accuracy of approximal caries detection was measured using a 5-point rating scale. Definite presence of caries was confirmed using a stereomicroscope. Analysis of caries detection data was performed by calculating sensitivity and specificity using repeated measures with ANOVA. Results: Significant differences were found in complete negative predictive value, absolute negative predictive value and complete dentine sensitivity value between different scan times (p< 0.05). These values were significantly different at 10 min, 60 min and 120 min (p< 0.05). However, immediate scan and 30 min delay were not significantly different (p> 0.05). The accuracy of approximal caries detection at 120 min was less than at 60 min and at 60 min was less than at 30 min. Conclusion: In order to detect approximal caries more accurately, DIGORA PSPs should be scanned within 30 min after exposure.